Recepcja źródeł ascetycznych i monastycznych w "Liber manualis" Dhuody z Septymanii (ok. 803-843) - Chudzikowska-Wołoszyn, Małgorzata (Vox Patrum, 2018)
The analysis of monastic and ascetic sources concluded in Liber manualis is the main goal of this article. The author is trying to systematize borrowings which Carolingian scientist quoted or paraphrased in her own treaty. The deep exploration of mentioned quote will allow us to determine a compilation and interpretation method which accompany to early Middle Ages scientist. Above and beyond it will let us to ask some research questions about intellectual formation of marchioness from Uzès, her access to tomes, creative awareness and orientation in political and religious changes taking place in a Country.